2011
DOI: 10.1038/modpathol.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the prevalence of Epstein–Barr virus-positive diffuse large B-cell lymphoma of the elderly: a comparative analysis of a Mexican and a German population

Abstract: Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma of the elderly was included as a provisional entity in the 2008 WHO lymphoma classification. Most reports of this disease come from Asia and little is known about it in other regions of the world, including Latin America. Therefore, in this study, 305 diffuse large B-cell lymphomas in patients above 50 years were analyzed, 136 from Mexico and 169 from Germany. EBV was detected by Epstein-Barr early RNA (EBER) in situ hybridization. Only cases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 21 publications
11
106
1
Order By: Relevance
“…10 In addition, EBV gene expression exhibited particular characteristics, given that previous studies suggested that EBV1 DLBCL in elderly patients generally have viral latency type II or III pattern. 8,10,14,15 We observed differences in the viral gene levels and protein expression, in cases with more than 20% of positive cells and those with less than 20% of positive cells. This fact leads us to define EBV patterns in the former group, whereas, due to the small amount of EBERs1 cells, the EBV latency could not be defined in the latter, even though morphological and immunophenotypic properties were similar in both groups.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…10 In addition, EBV gene expression exhibited particular characteristics, given that previous studies suggested that EBV1 DLBCL in elderly patients generally have viral latency type II or III pattern. 8,10,14,15 We observed differences in the viral gene levels and protein expression, in cases with more than 20% of positive cells and those with less than 20% of positive cells. This fact leads us to define EBV patterns in the former group, whereas, due to the small amount of EBERs1 cells, the EBV latency could not be defined in the latter, even though morphological and immunophenotypic properties were similar in both groups.…”
Section: Discussionmentioning
confidence: 83%
“…27 In contrast to the first publications, 3,45 most recent reported series-including ours-have found a predominant nodal presentation. 9,10,14,46 Morphologically, the distinction between the polymorphic and the monomorphic subtype is no longer regarded as clinically relevant. 8 Although several pathological characteristics have been described in EBV1 LDBCL of the elderly, we also corroborated that there is no morphologic or immunohistochemical pattern that is specific of this entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 Currently, age-related EBV-positive lymphoproliferative disorder accounts for 8-10% of diffuse large B-cell lymphoma cases among East Asian patients with no predisposing immunodeficiency; 4,8,9 however, little information is available about the frequency of this condition in western countries. 4,[10][11][12] The largest western series published to date, 11 including other EBV-positive lymphoproliferative lesions (reactive lymphoid hyperplasia, polymorphic extranodal, polymorphic nodal and diffuse large B-cell lymphoma), demonstrates that the spectrum of EBV-related lesions in western populations is wider than previously expected and mirrors the situation found in Asian countries. In addition, a direct comparison between the prevalence of this particular neoplasm between Mexican and German populations demonstrates that EBVpositive diffuse large B-cell lymphoma of the elderly in a Latin-American (Mexican) population has a similar prevalence, comparable with what has been reported in Asian countries, and in contrast to the low frequency in western populations (1-3%).…”
mentioning
confidence: 86%
“…Additionally, geographic differences could be explained by different strains of EBV. For example, a high frequency of EBV type B with the LMP1 30bp deletion was found in Mexican cases [6].…”
Section: Risk Stratificationmentioning
confidence: 99%